A mid-IR study of Hickson compact groups: II. Multiwavelength analysis of the complete GALEX-Spitzer sample - Bitsakis, T; Charmandaris, V; Da Cunha, E; Díaz-Santos, T; Le Floc'H, E; Magdis, G (2011)
We present a comprehensive study of the impact of the environment of compact galaxy groups on the evolution of their members using a multiwavelength analysis from the ultraviolet to the infrared, for a sample of 32 Hickson compact groups (HCGs) containing 135 galaxies. Fitting the spectral energy distributions (SEDs) of all galaxies with the state-of-the-art model of da Cunha et al. (2008, MNRAS, 388, 1595) we can accurately calculate their mass, SFR, and extinction, as well as estimate their infrared luminosity and dust content. We compare our findings with samples of field galaxies, early-stage interacting pairs, and cluster galaxies with similar data. We find that classifying the groups as dynamically "old" or "young", depending on whether at least one quarter of their members are early-type systems, is physical and consistent with past classifications of HCGs based on their atomic gas content. Dynamically "old" groups are more compact and display higher velocity dispersions than "young" groups. Late-type galaxies in dynamically "young" groups have specific star formation rates (sSFRs), NUV-r, and mid-infrared colors that are similar to those of field and early-stage, interacting pair spirals. Late-type galaxies in dynamically "old" groups have redder NUV-r colors, because they have likely experienced several tidal encounters in the past, thereby building up their stellar mass, and display lower sSFRs. We identify several late-type galaxies that have sSFRs and colors similar to those of elliptical galaxies, since they lost part of their gas due to numerous interactions with other group members. Also, 25% of the elliptical galaxies in these groups have bluer UV/optical colors than normal ellipticals in the field, probably due to star formation as they accreted gas from other galaxies of the group or via merging of dwarf companions. Finally, our SED modeling suggests that in 13 groups, ten of which are dynamically "old", there is diffuse cold dust in the intragroup medium. All this evidence points to an evolutionary scenario in which the effects of the group environment and the properties of the galaxy members are not instantaneous. Early on, the influence of close companions to group galaxies is similar to the one of galaxy pairs in the field. However, as the time progresses, the effects of tidal torques and minor merging shape the morphology and star formation history of the group galaxies, leading to an increase in the fraction of early-type members and a rapid build up of the stellar mass in the remaining late-type galaxies. © 2011 ESO.